Three-dimensional omnidirectional characterization methods of rock anisotropic wave velocity and acoustic emission location optimization - Shengjun MIAO; Wenxuan YU; Mingchun LIANG; Pengjin YANG; Conghao LI; Zejing LIU (工程科学学报)
Rock failure and instability have been key research topics in rock mechanics domestically and internationally. Numerous geotechnical disasters, such as rock bursts and slope instability, are associated with these phenomena. Acoustic emission detection is recognized as an effective method for monitoring rock failure and instability processes. Uniaxial compression tests were carried out on marble and siltstone to investigate the anisotropic characteristics of rock wave velocity and their influence on the accuracy of acoustic emission location. Prior to reaching the peak, marble remains predominantly in the elastic stage, with the average wave velocity remaining nearly constant. The horizontal wave velocity is consistently higher than the oblique longitudinal wave velocity, indicating fewer longitudinal cracks in the initial state. In the compaction stage of siltstone, horizontal, oblique longitudinal, and average wave velocity show an increasing trend. During the elastic stage, the horizontal and average wave velocities decrease slowly, indicating the presence of small longitudinal fractures. In the damage stage, the horizontal, oblique longitudinal and average wave velocities decrease rapidly, signifying that the fractures have propagated. A 3D ellipsoid characterization method for rock anisotropic wave velocity using the Rodrigues matrix is proposed in accordance with the characteristics of rock wave velocity evolution in different directions. The long axis of the ellipsoid represents the maximum wave velocity within the rock, whereas the short axis reflects the minimum wave velocity. During the compression of marble, the maximum and minimum wave velocities in various directions remain relatively stable until the peak stress is reached. By contrast, for siltstone, the maximum wave velocity increases during the compaction phase, whereas the minimum wave velocity remains constant. In the damage stage, the minimum wave velocity decreases due to rock damage and crack formation, whereas the maximum wave velocity remains unaffected. The statistical results indicate that the azimuth of the wave velocity ellipsoid for marble and siltstone is over 77% consistent with the crack azimuth. This finding suggests that the method can effectively predict crack propagation. In addition, an acoustic emission location method that incorporates the anisotropic wave velocity evolution characteristics is proposed. The average error of the proposed method is determined to be 1.89 mm for marble and 2.76 mm for siltstone, as measured by the lead breaking test. The location error for siltstone is greater than that for marble due to three primary reasons. First, siltstone exhibits high porosity, resulting in unstable and noisy acoustic emission signals, which complicate the extraction of the received signals. Second, the wave velocity of siltstone varies at different stages, displaying distinct changing trends and significant amplitude fluctuations. Lastly, siltstone demonstrates stronger wave velocity anisotropy, with inconsistent variation trends observed across different stages. Compared with traditional simplex and Geiger methods, the positioning accuracy of the proposed method improves by more than 58% in both rock types, validating the effectiveness of the proposed location method. In addition, this method is applicable to microseismic positioning, offering a more accurate solution for monitoring and early warning in geotechnical engineering disasters.